Activities of Key Enzymes Involved in Starch Accumulation In Sorghum (Sorghum Bicolor L. Moench) Grains With Different Starch Contents - Zhou, Yufei; Zhang, Ruidong; Yi, Bing; Wang, Yitao; Xing, Yifan; Jiang, Bing; Li, Bang; Xu , Xiaoxue; Chen, Xiaofei (Bangladesh Journal of Botany, 2022)
Starch accumulation and the seven metabolic enzyme activities in sorghum grains with different starch contents were investigated under field conditions in Shenyang Agricultural University. The results indicated that the starch accumulation in Tieza17 (high starch content variety) and Liaoza11 (low starch content variety) grains could be fitted with logistic equation. The activities of sucrose synthase (SS), soluble starch synthase (SSS) and uridine diphosphate glucose pyrophosphorylase (UGPase) in Tieza17 were similar to those in Liaoza11. Adenosine diphosphate glucose pyrophosphorylase (AGPase) and granule-bound starch synthase (GBSS) activities in Tieza17 grains were consistently higher than those in Liaoza11 grains. Starch branching enzyme (SBE) and starch debranching enzyme (DBE) activities increased or decreased significantly between the two varieties at different filling stages. It is suggested that the differences in the activities of AGPase, GBSS, SBE and DBE and their tradeoff played an important role in regulating starch accumulation in sorghum grains. Bangladesh J. Bot. 51(2): 217-222, 2022 (June)